Amine-functionalized Metal-Organic Frameworks: An Efficient and Recyclable Heterogeneous Catalyst for the Knoevenagel Condensation Reaction - Taher, Abu; Lee, Dong-Jin; Lee, Byoung-Ki; Lee, Ik-Mo (Synlett, 2016)
A highly efficient and reusable catalyst based on metal-organic frameworks (MOF) has been synthesized by post-functionalization and applied in Knoevenagel condensations of various aldehydes and ketones. The catalytic efficiency was demonstrated by the high conversion (over 85−98%) of the reactants under mild conditions. The catalyst maintained its unique framework after the reaction and could be recycled and reused several times without significant loss of activity.
Keywords: Knoevenagel condensation; metal-organic frameworks; heterogeneous catalysis; carbon–carbon bond; aldehyde; ketone